Quality of Accounting Information Systems as An Agency Theory Problem on State-Owned Enterprises in Indonesia - Nasution, Yan Noviar; Fadillah, Haqi (Jurnal Kajian Akuntansi, 2022)
AbstractThis research aims to prove the effect of information technology implementation and top management support on the quality of accounting information systems as one solution to the problem of agency theory, which is measured through the level of information technology implementation activities and top management support to suppress information asymmetry. Data were analyzed using the Structural Equation Model (SEM) method from a questionnaire given to 106 States Own Enterprises. There are 3 respondents in each enterprise so the total respondents are 318 people. 280 questionnaires were returned and could be processed (response rate of 88%). The results showed that the application of information technology and top management support had a positive effect on the quality of accounting information systems. The better the support of top management, the better the quality of accounting information systems. Furthermore, partially and simultaneously the implementation of information technology and top management support play an important role in improving the quality of accounting information systems, as well as in helping to solve agency problems.Keywords: Agency theory; Implementation of information technology; Quality of accounting information systems; Top management supportÂ Abstrak Penelitian ini bertujuan untuk membuktikan pengaruh penerapan teknologi informasi dan dukungan manajemen puncak terhadap kualitas sistem informasi akuntansi sebagai salah satu solusi permasalahan teori keagenan, yang diukur melalui tingkat aktivitas implementasi teknologi informasi dan dukungan manajemen puncak untuk menekan asimetri informasi. Data dianalisis menggunakan metode Structural Equation Model (SEM) dari kuesioner yang diberikan kepada 106 BUMN. Pada masing-masing BUMN terdapat 3 orang responden sehingga total responden berjumlah 318 orang. Dari jumlah tersebut, kuesioner kembali dan dapat diolah sebanyak 280 kuesioner (response rate sebesar 88%). Hasil penelitian menunjukkan bahwa penerapan teknologi informasi dan dukungan manajemen puncak berpengaruh positif terhadap kualitas sistem informasi akuntansi. Semakin baik dukungan manajemen puncak, semakin baik kualitas sistem informasi akuntansi. Selanjutnya, secara parsial dan simultan penerapan teknologi informasi dan dukungan manajemen puncak berperan penting dalam peningkatan kualitas sistem informasi akuntansi, serta dalam membantu menyelesaikan masalah keagenan.Kata Kunci: Dukungan manajemen puncak; Kualitas sistem informasi akuntansi; Penerapan teknologi informasi; Teori agensi